Magnetic nanoparticle-induced hyperthermia with appropriate payloads: Paul Ehrlich's "magic (nano)bullet" for cancer theranostics?. (November 2016) - Datta, N.R.; Krishnan, S.; Speiser, D.E.; Neufeld, E.; Kuster, N.; Bodis, S.; Hofmann, H.
Highlights: Magnetic nanoparticles with appropriate payloads as cancer theranostic agents. Critical payloads to offer personalised cancer diagnosis and therapy. Thermochemoradiotherapy, immunotherapy and gene-silencing could be offered. Treatment planning for thermal dosimetry with magnetic nanoparticles is feasible. Magnetic nanoparticles could thus realise Paul Ehrlich's "magic (nano)bullet." Abstract: Effective multimodal cancer management requires the optimal integration of diagnostic and therapeutic modalities. Radiation therapy, chemotherapy and immunotherapy, alone or in combination, are integral parts of various cancer treatment protocols. Hyperthermia at 39–45 °C is a potent radiosensitiser and has been shown to improve therapeutic outcomes in various tumours through its synergy with chemotherapy. Gene silencing approaches, using small interfering RNAs and microRNAs, are also being explored in clinical trials in oncology. The rapid developments in multifunctional nanoparticles provide ample opportunities to integrate both diagnostic and therapeutic modalities into a single effective cancer "theranostic" vector. Nanoparticles could extravasate passively into the tumour tissues in preference to the adjacent normal tissues by capitalizing on the enhanced permeability and retention effect. Tumour targeting might be further augmented by conjugating tumour-specific peptides and antibodies onto the surface of these nanoparticles or by activation through electromagnetic radiations, laser or ultrasound. Magnetic nanoparticles can induce hyperthermia in the presence of an alternating magnetic field, thereby multifunctionally with tumour-specific payloads empowering tumour specific radiotheranostics (for both imaging and radiotherapy), chemotherapy drug delivery, immunotherapy and gene silencing therapy. Such a (nano)bullet could realise the "magic bullet" conceived by Paul Ehrlich more than a century ago. This article discusses the various aspects of this "magic (nano)bullet" and the challenges that need to be addressed to usher in this new paradigm in modern cancer diagnostics and therapeutics.